The Influence of Trade Unions, Policies, HR Innovation, and Engagement on Employee Rights and Welfare Protection Post-PT Sritex Layoffs (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study explores the influence of trade unions, employment policies, human resource (HR) innovation, and employee engagement on the protection of rights and welfare of employees after mass layoffs at PT Sritex. The research is motivated by the urgency to understand how organizational mechanisms and policy-related factors affect workers’ well-being in the aftermath of large-scale layoffs, especially in labor-intensive industries facing global competition. Using a quantitative approach, the study employed a structured questionnaire distributed to 100 former and current employees of PT Sritex. Data were analyzed through multiple linear regression using the Statistical Package for the Social Sciences (SPSS) to measure the relationship and significance between the independent and dependent variables. The findings demonstrate that trade unions and employment policies have a significant positive impact on the protection of employee rights and welfare, ensuring that employees retain basic security even after layoffs. HR innovation also contributes by providing adaptive strategies and sustainable practices for workforce restructuring. Furthermore, employee engagement is found to play a crucial mediating role in strengthening organizational commitment, improving psychological resilience, and maintaining trust among employees during difficult transitions. Collectively, these four variables exhibit strong predictive power in determining welfare outcomes, emphasizing the importance of an integrated approach. This study highlights that collaboration between trade unions, policymakers, and corporate leaders is essential in strengthening employee protections. A balanced framework combining responsive policies, innovative HR practices, and active worker participation provides both immediate and long-term benefits. The practical implications of this research encourage companies and government institutions to design restructuring strategies that not only ensure operational sustainability but also safeguard employee rights, dignity, and welfare in times of uncertainty.